O trágico na Trilogia Tebana de Sófocles - Milan, Marilei Golfe (2022)
Works with the tragic theme have attracted many readers over time, this fact is confirmed by the search for classical works, re-scriptures of plays and publications on the subject. Overthe centuries, the presence of works of antiquity as primordial for the study and elaboration of texts on tragedy has been observed. Thus, this dissertation aims to understand the tragic in classical Greek literature. It is intended to identify the themes in the plays that make up the Tebana Trilogy, which are three, Oedipus King, Oedipus in Colonus and Antigone, written by the Greek poet Sophocles. In the light of the theories presented, the corpora is extracted to elaborate this study, in the sense of the hero's excess of passions, suffering as a form of redemption and adjustments in the face of the conflicting perplexity of the human being. In view of the tragic in classical Greek literature, the research is exploratory and bibliographic with a qualitative approach. For this, Aristotle (2017), Brandão (2015), Lesky (1996), Vernant (1979, 1999, 2002), Weyne (1984), and the philosopher Nietzsche (2006, 2007, 2014, 2015), offer us the theoretical basis of this study. The result obtained in this research showed the attempt to disobey the tragic destiny by the hero, who in his tyrant wisdom sacrificed the gift of vision and attained death, not before his redemption, and left conflicts of inheritance to the descendants, who had to dispose of their human validity in the face of the unwritten laws of the divine powers. Thus, the research opportunistized the literary understanding of the tragic and also about the effect of the tragic, this added in the spectator learning by the purification of emotions, an experience provided by the tragic pieces that make up the Tebana Trilogy.